Clinical use of donation after circulatory death pancreas for islet transplantation. Issue 9 (4th March 2021) - Doppenberg, Jason B.; Nijhoff, Michiel F.; Engelse, Marten A.; de Koning, Eelco J. P.
Abstract : Due to a shortage of donation after brain death (DBD) organs, donation after circulatory death (DCD) is increasingly performed. In the field of islet transplantation, there is uncertainty regarding the suitability of DCD pancreas in terms of islet yield and function after islet isolation. The aim of this study was to investigate the potential use of DCD pancreas for islet transplantation. Islet isolation procedures from 126 category 3 DCD and 258 DBD pancreas were performed in a 9‐year period. Islet yield after isolation was significantly lower for DCD compared to DBD pancreas (395 515 islet equivalents [IEQ] and 480 017 IEQ, respectively; p = .003). The decrease in IEQ during 2 days of culture was not different between the two groups. Warm ischemia time was not related to DCD islet yield. In vitro insulin secretion after a glucose challenge was similar between DCD and DBD islets. After islet transplantation, DCD islet graft recipients had similar graft function (AUC C‐peptide) during mixed meal tolerance tests and Igls score compared to DBD graft recipients. In conclusion, DCD islets can be considered for clinical islet transplantation. Abstract : This single‐center retrospective study compares 126 donation after circulatory death and 258 donation after brain death pancreatic islet isolations and demonstrates despite a substantially lower islet yield, islets from donation after circulatory death are as functional in vitro as in vivo in humans.